Detection of Epstein-Barr Virus in 130 Cases of Eyelid Sebaceous Gland Carcinoma Using In Situ Hybridization. (1st April 2020) - Gao, Huanhuan; Tang, Lijuan; Lin, Jianxian; Zhang, Wenxin; Li, Yongping; Zhang, Ping
Abstract : Purpose . In this study, we aimed to investigate the presence of Epstein–Barr virus (EBV) in the eyelid sebaceous gland carcinoma (SGC) and its association with the clinicopathologic features. Methods . One hundred and thirty paraffin-embedded SGC specimens were retrieved from the Clinical Pathology Department of Zhongshan Ophthalmic Center. Epstein–Barr virus-encoded RNA (EBER) was detected with in situ hybridization (ISH) using the Leica BOND system autostainer. The age and gender distributions of all patients were analyzed and compared with earlier reports. Pearson's χ 2 and Fisher's exact tests were used to determine the association between clinicopathological features such as age, gender, laterality eye, tumor basal dimension, degree of tumor differentiation, and EBER positivity. Likewise, the relationship between the grade and tumor basal dimension in EBER-positive SGC of the eyelid was analyzed. Results . Thirty-four out of one hundred and thirty (26.2%) eyelid SGC specimens were positively stained for EBER. The age range of highest incidence was 46–75 years, and the female to male ratio was 1 : 0.9. No significant correlation was found between EBER-positivity and age (p = 0.5370 ), gender (p = 0.4758 ), and degree of tumor differentiation (p = 0.7787 ). However, EBV positivity was strongly correlated with the right eye (p = 0.0287 ), the tumor basal dimension (p = 0.0001 ). EBV positivity grade presented statistically associated with tumor size (p = 0.0329 ). Conclusion . We conclude that ISH is a sensitive method to identify EBV in SGC of the eyelid. A possible causal association of EBV in SGC patients is suggested by high frequency of EBER-ISH positivity and its association with the clinicopathologic features.